Gender-Based Differences in COPD Patients with Type 2 Respiratory Failure—Impact on Clinical Practice - Tarkan Ozdemir; Murat Yıldız; Maşide Arı; Emrah Arı; Güler Eraslan Doğanay; Mustafa Özgür Cırık; Melek Doğancı; Çiğdem Özdilekcan; Derya Kızılgöz; Yusuf Tuğrul Şipit (Medicina)
Background and Objectives: To contribute to clinical practice by identifying gender-based differences in patients diagnosed with chronic obstructive pulmonary disease (COPD) who are monitored in the intensive care unit due to type 2 respiratory failure. Materials and Methods: The study was planned as a prospective, observational, and cross-sectional investigation. A total of 258 patients, 91 females and 167 males, were included in the study between 2023 and 2024. Demographic data and clinical parameters of COPD patients admitted to intensive care due to hypercapnic respiratory failure and treated with noninvasive ventilation (NIV) were compared between genders. Results: The number of male patients was higher than female patients, while the mean age of female patients was higher than that of males. The body mass index (BMI), morbid obesity, atrial fibrillation, renal disease, heart failure, hypertension, hypothyroidism, the Charlson Comorbidity Index (CCI), and the cardiothoracic ratio were found to be significantly higher in female patients. Emphysema and steroid use in treatment were more common in male patients. In laboratory analyses conducted at the time of admission, the average D-dimer and brain natriuretic peptide (BNP) levels were higher in female patients. The mean arterial carbon dioxide pressure (PaCO2) level assessed prior to discharge was also higher in female patients. Conclusions: Heart failure and risk factors that may lead to heart failure are more prominent in female COPD patients with type 2 respiratory failure. Despite the lower number of female patients compared to males, the significantly higher comorbidity burden in females, as per CCI scores, suggests that medical processes may be more challenging to manage in females. We believe that these findings will contribute to clinical practice and provide clinicians with insights for patient management.